Neotropical Stomopogon (Diptera, Muscidae): new species, redescriptions and key to species - Fogaça, João M.; Gomes, Lucas R. P.; Couri, Márcia S.; Rodríguez-Fernandez, Jaime I.; de Carvalho, Claudio J. B. (Zootaxa, 2021)
Stomopogon Malloch (Diptera, Muscidae) is a Neotropical genus recorded from Argentina, Bolivia, Brazil, Chile and Peru. In this contribution, the genus is revised, and three new species are described, one from Bolivia (Murillo, La Paz), one from Brazil (Palmas, Paraná) and one from Peru (Wayqecha, Cuzco). The descriptions include color images, illustrations and ultrastructural morphology of the terminalia of the adult. We provide an identification key to the species of Stomopogon and an updated map with species’ distributions. Stomopogon acuta (Malloch, 1934) is proposed as a new junior synonym of S. inculta Stein, 1911.